Modulation of Hoogsteen dynamics on DNA recognition - Yu Xu (Nature Portfolio, 2018)
DNA is found in a dynamic equilibrium between standard Watson-Crick (WC) base pairs and non-standard Hoogsteen (HG) base pairs. Here the authors describe the influence of echinomycin and actinomycin D ligands binding on the HG-WC base pair dynamics in DNA.